2022
DOI: 10.1111/1541-4337.13086
|View full text |Cite
|
Sign up to set email alerts
|

Composition, processing, and quality control of whole flaxseed products used to fortify foods

Abstract: Whole flaxseed (flour) as a good source of omega‐3 fatty acid and phytochemicals with excellent nutritional and functional attributes has been used to enrich foods for health promotion and disease prevention. However, several limitations and contemporary challenges still impact the development of whole flaxseed (flour)‐enriched products on the global market, such as naturally occurring antinutritional factors and entrapment of nutrients within food matrix. Whole flaxseed (flour) with different existing forms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 174 publications
1
14
0
Order By: Relevance
“…Furthermore, an ALA-rich diet helps in reduction of hepatic lipid deposition both by stimulating β oxidation and by inhibiting fatty acid synthesis (Hussein et al, 2014). An earlier study by Zhang et al (2022) also supported this study analyses as it showed significant reduction in TC (22%) and LDL-c (24%) among hypercholesterolemic patients after 8 weeks of consuming 600 mg/day SDG derived from flaxseeds (Torkan et al, 2015). The same outcomes were obtained in a second research in which volunteers received a single 500 mg dosage of trans-anethole for 7 weeks (12 mg/kg body weight) in order to manage hyperlipidemia in patients (Mehra et al, 2021).…”
Section: Plasma Lipidsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, an ALA-rich diet helps in reduction of hepatic lipid deposition both by stimulating β oxidation and by inhibiting fatty acid synthesis (Hussein et al, 2014). An earlier study by Zhang et al (2022) also supported this study analyses as it showed significant reduction in TC (22%) and LDL-c (24%) among hypercholesterolemic patients after 8 weeks of consuming 600 mg/day SDG derived from flaxseeds (Torkan et al, 2015). The same outcomes were obtained in a second research in which volunteers received a single 500 mg dosage of trans-anethole for 7 weeks (12 mg/kg body weight) in order to manage hyperlipidemia in patients (Mehra et al, 2021).…”
Section: Plasma Lipidsupporting
confidence: 72%
“…The flour's particle size index, moistness, and the type of fat used are the three main components that determine the spread factor of cookies while baking (Man et al, 2021). Spread ratio, which in turn is impacted by the relative water availability of various components and the capacity of wheat or any other component to absorb moisture during dough production, also has an impact on cookie diameter and thickness (Zhang et al, 2022).…”
Section: Physical Parameters Of Cookiesmentioning
confidence: 99%
“…Linseeds polyphenols such as SDG have multiple biological functions such as antioxidant, anti-inflammatory, anti-cancer and antimicrobial activities. Nowadays there is interest in using whole linseed (flour) as functional food ingredients owing to the healthier and more sustainable properties than those of isolated linseed ingredients [ 27 ]. Moreover, recent studies suggested that Linseed lignans found in grain flour can be used as a good antioxidant for improving the stability of linseed oil incorporated into functional foods [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…For dry pasta at 90 °C, the P10 treatment showed greater hardness when compared to the other treatments, showing a weaker network when using lower drying temperatures (60 °C and 80 °C). The hardness of pasta analysed by breaking was influenced by AF incorporation, due to gluten network dissolution and the more porous structure of the fibres compared to wheat flour, which leads to pasta with a higher moisture content and lower hardness (Zhang et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%